FRACTIONAL FLOW RESERVE–GUIDED PCI IN PATIENTS WITH MULTI-VESSEL CORONARY ARTERY DISEASE - BASIT , A; YUSRA, .; MEMON , AQ; ULLAH , Z; IRSHAD , M; ILYAS , MA; ABDULLAH , M (Biological and Clinical Sciences Research Journal, 2024)
In multi-vessel coronary artery disease (CAD), there is insufficient data to support the use of fractional flow reserve (FFR) to guide treatment beyond candidates for coronary graft surgery or percutaneous coronary intervention. Objectives: The purpose of this study was to investigate whether the treatment based on FFR is more effective in lowering the ‘cumulative rate of death’, ‘myocardial infarction’, ‘stroke, or unexpected coronary revascularization in patients who have multi-vessel CAD than a ‘traditional strategy based on coronary angiography without FFR’. Methodology: A retrospective cross-sectional study involving 1200 participants, i-e, 607 in the control group and 593 in the FFR group. This study was conducted at the National Institute of Cardiovascular Diseases (NICVD) from June 2021 to July 2022. Multi-vessel CAD candidates were randomised (1 to 1) to either a conventional treatment plan without FFR or an intervention plan ‘based on FFR in all stenotic (≥50%) coronary arteries. ‘Revascularization (percutaneous coronary intervention or surgery)’ was recommended for FFR ≤0.80 lesions in the FFR group. A significant ‘adverse cardiac or cerebrovascular event at one year served as the primary outcome. Results: After a safety investigation and the enrollment of 1200 patients, the data safety and monitoring board decided to terminate the trial early. The results showed no appreciable variations in the frequencies of major adverse cardiac or cerebrovascular events among the FFR and control groups at the one-year monitoring, according to intention to treat. A 24-month extended follow-up confirmed no significant difference in all-cause mortality between the FFR group and the control group. More individuals were referred solely for medical care when FFR dramatically decreased the percentage of revascularised individuals. Conclusion: An FFR-guided approach reduced revascularisation rates compared to angiography only and almost doubled the rate of OMT alone among individuals with multi-vessel coronary artery disease. However, the FFR-guided approach had no discernible impact on the clinical results at one year, determined mainly by the SYNTAX score and left ventricular function. The current study indicates that while FFR alone does not affect clinical results, it does assist in selecting the best revascularisation approach.